Multiple interactions between the alpha2C- and beta1-adrenergic receptors influence heart failure survival - Case Karen L; Hahn Harvey S; Grabowski Gregory A; Aronow Bruce J; Keddache Mehdi A; Kelly Reagan J; Kardia Sharon LR; Wagoner Lynne E; Dorn Gerald W; Liggett Stephen B (BMC, 2008)
Abstract Background Persistent stimulation of cardiac β1-adrenergic receptors by endogenous norepinephrine promotes heart failure progression. Polymorphisms of this gene are known to alter receptor function or expression, as are polymorphisms of the α2C-adrenergic receptor, which regulates norepinephrine release from cardiac presynaptic nerves. The purpose of this study was to investigate possible synergistic effects of polymorphisms of these two intronless genes (ADRB1 and ADRA2C, respectively) on the risk of death/transplant in heart failure patients. Methods Sixteen sequence variations in ADRA2C and 17 sequence variations in ADRB1 were genotyped in a longitudinal study of 655 white heart failure patients. Eleven sequence variations in each gene were polymorphic in the heart failure cohort. Cox proportional hazards modeling was used to identify polymorphisms and potential intra- or intergenic interactions that influenced risk of death or cardiac transplant. A leave-one-out cross-validation method was utilized for internal validation. Results Three polymorphisms in ADRA2C and five polymorphisms in ADRB1 were involved in eight cross-validated epistatic interactions identifying several two-locus genotype classes with significant relative risks ranging from 3.02 to 9.23. There was no evidence of intragenic epistasis. Combining high risk genotype classes across epistatic pairs to take into account linkage disequilibrium, the relative risk of death or transplant was 3.35 (1.82, 6.18) relative to all other genotype classes. Conclusion Multiple polymorphisms act synergistically between the ADRA2C and ADRB1 genes to increase risk of death or cardiac transplant in heart failure patients.